Effectiveness of Educating Problem Solving and Decision making Skills on Mental health and Resilience of Female University Students - Amiri Majd, Mojtaba; Asgharpour, Safura; Ghiasvand, Marzieh (International Journal of Applied Behavioral Sciences, 2017)
Background: The term resilience is used in mental health to describe a person’s capacity to cope with changes and challenges, and to bounce back during difficult times. Good problem-solving and decision making skills help young people to think abstractly, reflectively and flexibly. Objectives: This study aimed to determine the effectiveness of educating problem solving skills and decision-making on mental health and resilience of female university students. Material and Methods: It was done through a quasi-experimental design with pre-test - post-test and control group. The sample consisted of 30 university students who were selected by convenience sampling and randomly assigned into experimental and control groups. The experimental group was trained in problem solving and decision-making for seven sessions of 2 hours. The assessment tool consisted of Ryff scales of psychological well-being (RSPWB), Symptom Checklist (SCL-25), and Connor-Davidson Resilience scale (CD-RISC). Data were analyzed by analysis of covariance. Results: The results showed that educating problem-solving and decision-making skills increased mental health and resiliency of female university students (p≤.05). Conclusion: It can be concluded that educating problem-solving and decision-making skills can promote mental health and resiliency and can be effective in preventing the incidence and severity of mental health problems.